Acute Intermittent Hypoxia Did Not Alter Pain Sensitivity or Pain Intensity Ratings for Individuals with Chronic Low Back Pain: A Pilot Study - George SZ; Horn ME (Journal of Pain Research, 2024)
Steven Z George,1,2 Maggie E Horn2 1Duke Clinical Research Institute, Duke University, Durham, NC, USA; 2Departments of Orthopaedic Surgery and Population Health Science, Duke University, Durham, NC, USACorrespondence: Steven Z George, Duke University, 300 Morgan Street, Office 480, Durham, NC, 27707, USA, Tel +1 919-668-0825, Email steven.george@duke.eduAims and Objective: The purpose of this pilot study was to explore whether AIH produces changes in pain sensitivity or in reports of self-reported pain intensity for individuals with low back pain.Methods: In a quasi-experimental, cross-over design we compared participants (n = 9) exposed to normal room air and hypoxia using a commercially available gas blender. The treatment period consisted of 5 consecutive days of randomly assigned to AIH or room air. For the participants initially randomized to AIH there was cross-over to receive 5 more consecutive days of room air. Therefore, this design allowed for between group and within subject assessment of AIH effects. Pain sensitivity was assessed with quantitative sensory testing (QST) for posterior superior iliac spine pressure threshold, plantar thermal threshold, and peak pain ratings. Self-reported pain intensity for low back pain was assessed via the Brief Pain Inventory.Results: There were no between group differences for AIH and room air in pain sensitivity or self-reported pain intensity. In the within subject analyses larger effect sizes favoring AIH were detected for plantar measures of pain sensitivity but not for self-reported pain intensity.Conclusion: This study, while presenting null findings, describes an initial step in determining whether AIH can be used to increase pain relief. Based on this pilot study we offer guidance for future research including study design, AIH dosage, participant selection, and using AIH in combination with non-pharmacologic treatments.Keywords: hypoxia, hypoalgesia, low back pain, pain sensitivity